2014
DOI: 10.1021/ef4022703
|View full text |Cite
|
Sign up to set email alerts
|

Shale Gas Potential of the Major Marine Shale Formations in the Upper Yangtze Platform, South China, Part III: Mineralogical, Lithofacial, Petrophysical, and Rock Mechanical Properties

Abstract: The marine black shale formations on the Upper Yangtze Platform, South China, are currently exploration targets for shale gas. Here, we report on the mineralogy, lithofacies, petrophysics, and rock mechanics of samples collected from the Ediacaran (Upper Sinian), Lower Cambrian, and Lower Silurian black shale intervals. All three formations are composed of high proportion of quartz, low content of clay, and rare or nonexistent content of carbonates. The Ediacaran and Lower Cambrian shales deposited in restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(93 citation statements)
references
References 45 publications
7
85
1
Order By: Relevance
“…It is typical marine sediment carbonaceous and black shale in the lower section and dark-grey silty shale in the upper section [22,23]. In recent years, many studies have been carried out on the lithofacies, geochemistry and mineralogy of the Niutitang Formation [21,24,25], although there is a lack of information on pore structure and fractal characteristics. Therefore, the aim of this study is to examine the pore structure and fractal characteristics of the Niutitang Formation from northwestern Hunan Province, China.…”
Section: Introductionmentioning
confidence: 99%
“…It is typical marine sediment carbonaceous and black shale in the lower section and dark-grey silty shale in the upper section [22,23]. In recent years, many studies have been carried out on the lithofacies, geochemistry and mineralogy of the Niutitang Formation [21,24,25], although there is a lack of information on pore structure and fractal characteristics. Therefore, the aim of this study is to examine the pore structure and fractal characteristics of the Niutitang Formation from northwestern Hunan Province, China.…”
Section: Introductionmentioning
confidence: 99%
“…Marine shales are widespread in the Yangtze Block, mainly in the Ediacaran Doushantuo Formation, the Lower Cambrian Niutitang Formation and the Lower Silurian Longmaxi Formation. These are some of the most promising strata for shale gas exploration in China (Dong et al, 2014;Tan et al, 2014aTan et al, , 2014bZou et al, 2011). Stratigraphic studies have indicated that the black shales in the Ediacaran Doushantuo Formation were mainly deposited in deep-water slope and basin settings (Jiang et al, 2011;Zhu et al, 2007); however, unlike the Cambrian and Silurian shales Han et al, 2013;Jiao et al, 2014;Liang et al, 2014;Ma et al, 2015;Tang et al, 2015;Tian et al, 2013Tian et al, , 2015Wang et al, 2015), the Ediacaran shales have not been described in great detail (Tan et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed to shed light on the porosity and pore structures of shales and the impact of shale composition on the pore development (Chalmers and Bustin, 2007;Chalmers et al, 2012a;Clarkson et al, 2013;Mastalerz et al, 2013;Milliken et al, 2013;Bustin, 2007, 2009a;Tan et al, 2014a). Since shales comprise fine-grained particles and abundant organic matter (OM), they commonly possess very low porosity and permeability due to continuous compaction and heating in the sedimentation process.…”
Section: Introductionmentioning
confidence: 99%
“…This difference accounts for the shift of the minimum strength orientation as pressure increases, and the locus of minimum strength value was predicted by the variable τ 0 and tanφ theory showed in the former curves. In the research of Tan et al, the uniaxial strength of Longmaxi black shale was affected by both the sample composition and the porosity, and brittle character was also revealed by triaxial compression test with confining pressure increasing up to 36 MPa [20].…”
Section: Discussionmentioning
confidence: 99%
“…Longmaxi formation from the Lower Silurian is composed of high proportion of quartz, low content of clay, and rare or nonexistent content of carbonates [20]. According to Tan's research, the Lower Silurian shales were deposited in a restricted marine basin environment and were formed during bottom water anoxic conditions; therefore, they were rarely influenced by bioturbation.…”
Section: Description Of the Studied Shalementioning
confidence: 99%